Effects of conditioners (standard, long term, and expander) on pellet quality and growth performance in nursery pigs - Johnston, S.L.; Hines, Robert H.; Maloney, C.A.; Traylor, S.L.; Sorrell, S.P.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In our first experiment, digestibilities for DM, N, and GE were greater and F/G was better for pigs fed pelleted diets than for pigs fed meal diets. However, we observed no advantages in ADG or F/G with long-term conditioning. In a second experiment, pelleting once again improved nutrient digestibility and F/G. Expander conditioning improved digestibilities of DM, N, and GE but not growth performance compared to standard conditioning.
Keywords: Swine; Nursery pigs; Pelleting; Expander conditioning